Strategi Inovatif Pelestarian Budaya Labuan Bajo: Integrasi Pendidikan, Digitalisasi, dan Pariwisata Berkelanjutan - Nasution, Delila Agustina; Siagian, Dewi Br; Sartika, Dian; Sitanggang, Engelni Mei; Damanik, Fatur Rahman; Azimah, Siti Syariah; Samosir, Katrina (QISTINA: Jurnal Multidisiplin Indonesia, 2025)
This research stems from the urgency to find innovative strategies for preserving the cultural heritage of Labuan Bajo amidst its rapid tourism development.The objective is to formulate an integrative preservation model by combining three key elements: education, digitalization, and sustainable tourism. Using a qualitative approach through literature study and policy analysis, this research proposes that the integration begins with incorporating Flores' local cultural content into the educational curriculum to build awareness among the younger generation. Furthermore, digitalization plays a role in documenting and promoting cultural assets, such as language, oral traditions, and crafts, through digital platforms like virtual museums and augmented reality, making them more accessible to both the youth and tourists. Ultimately, the element of sustainable tourism acts as an economic driver by developing authentic cultural tour packages and actively involving local communities as the main actors, ensuring that the economic benefits of tourism are directly felt and foster a sense of pride in preserving their culture. The study concludes that the synergy between education, digitalization, and sustainable tourism creates a mutually reinforcing cycle; education builds awareness, digitalization ensures accessibility and documentation, while sustainable tourism provides economic incentives, thereby guaranteeing the holistic and sustainable preservation of Labuan Bajo's cultural heritage.